Regulatory compliance,motivations and capacities in charcoal production in Baringo and Kitui counties, Kenya - Sola, P.; Gambo, J.; Muthui, R.; Amugune, I.; Wanjira, E.O.; Kitema, A. (World Agroforestry Centre, 2021)
Illegality in the forest sector is a major threat to forest and tree resources. Governments have responded by imposing more regulations and restrictions, with little consideration given to motivations for noncompliance. In Kenya, the Forest (Charcoal) Rules 2009 – while considered significant progress toward regulating the industry – have failed to elicit sufficient compliance to formalize the value chain and stem illegality. This study aimed to investigate the mandates, capacities, motivations and drivers for compliance by members of charcoal producer associations (CPAs), while examining the incentive mechanisms required to increase compliance in the charcoal value chains in Baringo and Kitui counties in Kenya. The study found that CPA members were engaged in the charcoal business mainly due to a lack of alternative livelihoods.